2023
DOI: 10.3390/ijms242015240
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Insights into Oxidative and Nitrative Modifications of DNA

Celia María Curieses Andrés,
José Manuel Pérez de la Lastra,
Celia Andrés Juan
et al.

Abstract: This review focuses on DNA damage caused by a variety of oxidizing, alkylating, and nitrating species, and it may play an important role in the pathophysiology of inflammation, cancer, and degenerative diseases. Infection and chronic inflammation have been recognized as important factors in carcinogenesis. Under inflammatory conditions, reactive oxygen species (ROS) and reactive nitrogen species (RNS) are generated from inflammatory and epithelial cells, and result in the formation of oxidative and nitrative D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 279 publications
0
4
0
Order By: Relevance
“…Guanine in DNA is converted to 8-OHdG upon free radical attack under oxidative stress ( Andrés et al, 2023 ). Compared to control retinas, the fluorescent intensity of the 8-OHdG markedly increased in water-fed COH eyes in the inner retina including RGC layer and the inner nuclear layer (INL), and slightly upregulated in the outer nuclear layer (ONL) ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Guanine in DNA is converted to 8-OHdG upon free radical attack under oxidative stress ( Andrés et al, 2023 ). Compared to control retinas, the fluorescent intensity of the 8-OHdG markedly increased in water-fed COH eyes in the inner retina including RGC layer and the inner nuclear layer (INL), and slightly upregulated in the outer nuclear layer (ONL) ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…The study revealed that the serum H 2 O 2 concentration of the chicks tended to decrease with increasing Met concentration at both 14 and 42 days old, suggesting that increasing the dietary Met concentration might affect intracellular and intercellular signaling in the organism. Hydroxyl radicals, which are potent oxidizing agents, can kill red blood cells and cause the degradation of DNA, cell membranes, and polysaccharide compounds ( Dizdaroglu and Jaruga, 2012 ; Andrés et al, 2023 ). The study revealed that increasing dietary methionine (Met) levels significantly reduced serum hydroxyl radical (·OH) concentrations in chicks at both 14 and 42 d of age, indicating potential health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Protein carbonylation causes degradation and aggregation, which impairs cellular function . On the other hand, in DNA, hydroxyl radicals cause major oxidative reactions by directly reacting with nitrogenous bases and deoxyribose . This process causes DNA fragmentation by the rupture of the nucleosome, which causes alteration to the structure of DNA within the chromatin .…”
Section: Toxicity Assessments Of Iron Oxidesmentioning
confidence: 99%
“…90 On the other hand, in DNA, hydroxyl radicals cause major oxidative reactions by directly reacting with nitrogenous bases and deoxyribose. 91 This process causes DNA fragmentation by the rupture of the nucleosome, which causes alteration to the structure of DNA within the chromatin. 64 The consequence of this reaction is gene alteration, which will affect cellular function.…”
Section: Toxicity Assessments Of Iron Oxidesmentioning
confidence: 99%